Humanized mouse models in MDS - Raluca Munteanu; Diana Gulei; Cristian Silviu Moldovan; Emanuele Azzoni; Laura Belver; Richard Feder; Simina Pirv; Anca Dana Buzoianu; Hermann Einsele; Moshe Mittelman; Gabriel Ghiaur; Robert Hasserjian; et al. (Cell Death and Disease)
Abstract Myelodysplastic syndromes (MDS) are heterogeneous hematopoietic stem cell disorders defined by ineffective hematopoiesis, multilineage dysplasia, and risk of progression to acute myeloid leukemia. Improvements have been made to identify recurrent genetic mutations and their functional roles, but translating this into preclinical models is still difficult. Traditional murine systems lack the human-specific cytokine support and microenvironmental support that is necessary to reproduce MDS pathophysiology. Humanized mouse models, particularly those incorporating human cytokines (e.g., MISTRG, NSG-SGM3, NOG-EXL), immunodeficient backgrounds, and co-transplantation strategies, have improved the engraftment and differentiation of human hematopoietic stem and progenitor cells. These models allow the study of clonal evolution, mutation-specific disease dynamics, and response to therapies in vivo. However, difficulties persist, such as limited long-term engraftment, incomplete immune reconstruction, and limited possibilities of modeling early-stage or low-risk MDS. This review presents an overview of current humanized and genetically engineered mouse models suitable for studying MDS, evaluating their capacity to replicate disease complexity, preserve clonal architecture, and support translational research. We highlight the need to develop new approaches to improve the actual methodologies and propose future directions for standardization and improved clinical relevance.